Use of direct practice as an active learning innovation - Aliyyah Chantika; Novy Fitria Wahyuni; Sandy Salim Alamsyah; Tegar Rifai (Curricula: Journal of Curriculum Development, 2022)
The learning process must be made as interesting as possible so that students can easily follow the learning itself. Many innovations have been developed to create exciting learning methods. In this case, the current learning model or method is increasingly varied and has a diverse focus. This research aims to develop learning using direct practice methods and see how these methods improve students' understanding of the material. The qualitative research method, with interviews as the data collection instrument. The subjects of this research are students of the 2021 batch of Business Education Study Program at Universitas Pendidikan Indonesia. The research sample collected was 15 students. The interview results show the influence of direct learning practice on students' understanding of learning materials. From the results of this study, it can be seen that the hands-on learning method is considered a learning method that is fun and interesting and makes it easier for educators to deliver material. Therefore, this method is very effective in improving understanding in students.